Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

India: apremier destination for outsourcing - Chorghade, Mukund S.; Chorghade, V. M.; Gurjar, Mukund K.; Ramana, Chepuri V.; Kamerkar, A. V.; Zafran, H.; Mashelkar, Raghunath Anant (Speciality Chemicals Magazine, 2005)

Stereoselective synthesis of (2S,7S)-7-(4-phenoxymethyl)2-(1-N-hydroxyureidyl-3-butyn-4-yl)oxepane: a potential anti-asthmatic drug candidate - Gurjar, M. K.; Rao, B. V.; Krishna, L. M.; Chorghade, Mukund S.; Ley, S. V. (Tetrahedron-Asymmetry, 2005)
We have achieved a short, efficient stereoselective synthesis of 7-membered oxepane derivatives with potential against asthma. Highlights of our synthetic strategy are regioselective oxidation of a hydroxyl group and efficient ring closure of an open chain aldehyde to a 2-benzenesulfonyl oxepane derivative with PhSO2H. Surprisingly the cis-isomer showed better activity than the traps-isomer. (C) 2005 Elsevier Ltd. All rights reserved.

Clay-mediated selective hydrolysis of 5 `-O-acetyl-2 `,3 `-isopropylidene/cyclohexylidene nucleosides - Gurjar, Mukund K.; Mondal, Dhananjoy; Ravindranadh, S. V.; Chorghade, Mukund S. (Synthetic Communications, 2006)
A generalized procedure for the selective hydrolysis of 5'O-acetyl-2',3'-isopropylidene/cyclohexylidene nucleosides with a solid catalyst, Montmorillonite K-10 in refluxing methanol, to furnish 5'-O-acetyl-nucleosides is described.
Keywords: 5-O-acetylnucleosides; isopropylidene-nucleoside hydrolysis; montmorillonite K 10

General strategy for a short and efficient synthesis of 3-hydroxy-4-methylprolines (HMP) - Mohapatra, Debendra K.; Mondal, Dhananjoy; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The non-proteinogenic amino acid 3-hydroxy-4-methylproline (HMP) is an active constituent of some potent antimicrobials including echinocandins, nostopeptins, pneumocandins, sporiofungin and mulundocandins. A synthesis has been achieved in 10 steps with 29% overall yield; the Evans' aldol reaction using Crimmins' modified method was pivotal to the success of the strategy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 3; 4-disubstituted proline; Crimmins' aldol reaction; Garner's aldehyde; non-proteinogenic amino acids; RUO4 mediated oxidation

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Protecting group directed ring-closing metathesis (RCM): the first total synthesis of an anti-malarial nonenolide - Mohapatra, Debendra K.; Ramesh, Dhondi K.; Giardello, Michael A.; Chorghade, Mukund S.; Gurjar, Mukund K.; Grubbs, Robert H. (Tetrahedron Letters, 2007)
The first synthesis of a newly found naturally occurring anti-malarial nonenolide is described. A pivotal step in the synthesis is the ring-closing metathesis of a dienoic ester prepared by coupling an acid and alcohol that were stereoselectively synthesized from (S)-alpha-hydroxy-gamma-butyrolactone and 1,2-O-isopropylidene D-glyceraldchyde, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-O-isopropylidene; anti-malarial agent; D-glyceraldehyde; Nonenolide; Ring-closing metathesis; Yamaguchi esterification

Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Syntheis of unusual tricyclic ring systems of biological interest - Mohapatra, Debendra K.; Maity, Pradip K.; Chorghade, Mukund S.; Gurjar, Mukund K. (Heterocycles, 2007)
We describe a new synthesis of tricyclic scaffolds that incorporate a fusion of triazole with 1,4-benzodiazepine utilizing intramolecular ``click'' chemistry.
Keywords: 1; 2; 3-Triazole; 4-benzodiazepine; Click chemistry; nitrogen rich polycyclic hetero-system; privileged structure

Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Practical syntheses of 4-fluoroprolines - Chorghade, Mukund S.; Mohapatra, Debendra K.; Sahoo, Gokarneswar; Gurjar, Mukund K.; Mandlecha, Manish V.; Bhoite, Nitin; Moghe, Santosh; Raines, Ronald T. (Journal of Fluorine Chemistry, 2008)
4-Fluoroprolines are among the most useful nonnatural amino acids in chemical biology. Here, practical routes are reported for the synthesis of the 2S, 4R, 2S, 4S, and 2R,4S diastereomers of 4-fluoroproline. Each route starts with (2S,4R)-4-hydroxyproline, which is a prevalent component of collagen and hence readily available, and uses a fluoride salt to install the fluoro group. Hence, the routes provide process-scale access to these useful nonnatural amino acids. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: 4-Fluoroproline; 4-Hydroxyproline; collagen; Nonnatural amino acid; Process-scale synthesis

Short total synthesis of (+)-cryptocarya diacetate - Gurjar, Mukund K.; Raghupathi, Neelarapu; Chorghade, Mukund S. (Heterocycles, 2009)
A short synthesis of (+)-cryptocarya diacetate was achieved by employing three component linchpin coupling, diastereoselective reduction of beta-hydroxyketone, and Z-selective HWE reaction as key transformations.
Keywords: Brook Rearrangement; cryptocarya diacetate; Diastereoselective Reduction; Horner-Wadswarth-Emmons Reaction; Linchpin coupling

Studies toward the total synthesis of carba analogue of motif C OF M. TB cell wall AG complex - Gurjar, Mukund K.; Reddy, Challa Nageswar; Kalkote, Uttam R.; Chorghade, Mukund S. (Heterocycles, 2009)
Herein we describe the synthesis of the carba analogue of motif C of arabinogalactan complex present in M tuberculosis cell wall. Pd(0) catalyzed allylic alkylation and Fraser-Reid's glycosidation are the two key reactions that were employed for the synthesis of central glycosyl accepter unit and the glycosylation respectively.
Keywords: Allylic Alkylation; desymmetrization; Fraser-Reid's Glycosidation; M. Tb Ag Complex; Mycobacterium tuberculosis